Structural optimization of the excavator boom under extreme working conditions using EDEM–ADAMS coupled simulation - Huawei Wu; Xiaolong Ding; Gui Liu; Xiaoyuan Zhu; Hualiang Wang (PLoS ONE, 2025)
Aiming at the extreme loading conditions of an backhoe loader under dynamic and uncertain environments, this paper proposes a structural optimization method based on EDEM-ADAMS for a compact multi-functional excavating transporter device. The D-H coordinate kinematic analysis model of the backhoe loader is constructed, and the forward kinematic solution is obtained. Using the multi-body dynamics software ADAMS and enhanced discrete element software, a virtual prototype model and a discrete element material model are established. Through the coupled simulation method of EDEM-ADAMS, the load distribution of two working modes, forward digging and side digging, is analyzed, and the extreme working conditions of the boom are determined. Finally, topology optimization of the boom under extreme working conditions is performed to strengthen the local structure. The results show that after optimization, the boom’s mass is reduced by 14.32 kg (13.80%), the maximum stress is reduced by 26.12%, and the total deformation is reduced by 29.11%. Compared to existing optimization methods, the equivalent stress and total deformation of the proposed optimized model are reduced by 18.76% and 22.27%, respectively. These improvements not only achieve weight reduction but also significantly enhance the structural strength and safety. The optimized design has significant implications for the structural optimization of similar backhoe loader under extreme working conditions.